Modeling, Simulation and Optimization of Complex Processes - HPSC 2012: Proceedings of the Fifth International Conference on High Performance Scientific Computing, March 5 - 9, 2012, Hanoi, Vietnam - Bock, Hans Georg; Hoang, Xuan Phu; Rannacher, Rolf; Schlöder, Johannes P. (Springer International Publishing Imprint: Springer, 2014)
Preface -- Hunter M. Brown, Minh Q. Phan, and Stephen A. Ketcham: A Non-Causal Inverse Model for Source Signal Recovery in Large-Domain Wave Propagation -- Roberto Croce, Daniel Ruprecht, and Rolf Krause: Parallel-in-Space-and-Time Simulation of the Three-Dimensional, Unsteady Navier-Stokes Equations for Incompressible Flow -- Martin L. Felis, Katja Mombaur, and Alain Berthoz: Mathematical Modeling of Emotional Body Language during Human Walking -- Fei Gao and Richard W. Longman: On Quadratic Programming Based Iterative Learning Control for Systems with Actuator Saturation Constraints -- Michael Griebel and Alexander Hullmann: A sparse grid based generative topographic mapping for the dimensionality reduction of high-dimensional data -- Markus Hansen, Claudia Schillings, and Christoph Schwab: Sparse Approximation Algorithms for High Dimensional Parametric Initial Value Problems -- Khai-Long Ho Hoang, Katja Mombaur, and Sebastian I. Wolf: Investigating Capturability in Dynamic Human Locomotion using Multi-Body Dynamics and Optimal Control -- Vitalii Yu. Kapitan and Konstantin V. Nefedev: High Performance Calculation of Magnetic Properties and Simulation of Nonequilibrium Phenomena in Nano_lms -- Galina Kurina: Inverse Problem of the Calculus of Variations for Second Order Differential Equations with Deviating Arguments -- Ping Lin, Minh Q. Phan, and Stephen A. Ketcham: State-Space Model and Kalman Filter Gain Identification by a Superspace Method -- Vu Thai Luan and Alexander Ostermann: Stiff Order Conditions for Exponential Runge{Kutta Methods of Order Five -- Andrea Manzoni, Toni Lassila, Alfio Quarteroni, and Gianluigi Rozza: A reduced-order strategy for solving inverse Bayesian shape identification problems in physiological flows -- Katja Mombaur: A mathematical study of sprinting on artificial legs -- Sabine Pickenhain: Hilbert Space Treatment of Optimal Control Problems with Infinite Horizon -- César de Prada, Smaranda Cristea, Rogelio Mazaeda, Luis G. Palacín: Optimum operation of a beer filltration process -- Nguyen Quang-Hung, Nam Thoai, Nguyen Thanh Son, and Duy-Khanh Le: Energy-Aware Lease Scheduling in Virtualized Data Centers -- Alexander Schubert, Katja Mombaur, and Joachim Funke: Mathematical Models of Perception and Generation of Art Works by Dynamic Motions -- Keh-Ming Shyue: An Eulerian interface-sharpening algorithm for compressible gas dynamics -- Tobias Steinle, Jadran Vrabec, and Andrea Walther: Numerical Simulation of the Damping Behavior of Particle-filled Hollow Spheres -- Hiroshi Umeo: FSSP Algorithms for Square and Rectangular Arrays -- Krzysztof Walkowiak and Jacek Rak: Optimization Issues in Distributed Computing Systems Design
Description based upon print version of record